Given, "(2xz - yz) dx + (2yz - xz) dy - (x^2- xy + y^2) dz = 0" .
Compare the given equation with "Pdx+Qdy+Rdz=0", we have
"P =2xz - yz, Q = 2yz-xz, R = -x^2+xy-y^2".
Given total differential equation is integrable if
"P(\\frac{\\partial Q}{\\partial z} - \\frac{\\partial R}{\\partial y}) + Q (\\frac{\\partial R}{\\partial x}-\\frac{\\partial P}{\\partial z}) + R (\\frac{\\partial P}{\\partial y}-\\frac{\\partial Q}{\\partial x})=0" .
For our problem:
"\\frac{\\partial Q}{\\partial z} = 2y -x, \\frac{\\partial R}{\\partial y}= x-2y, \\\\\n \\frac{\\partial R}{\\partial x} = -2x+y , \\frac{\\partial P}{\\partial z}=2x-y \\\\\n\\frac{\\partial P}{\\partial y} = -z = \\frac{\\partial Q}{\\partial x}" ,
Hence,
"P(\\frac{\\partial Q}{\\partial z} - \\frac{\\partial R}{\\partial y}) + Q (\\frac{\\partial R}{\\partial x}-\\frac{\\partial P}{\\partial z}) + R (\\frac{\\partial P}{\\partial y}-\\frac{\\partial Q}{\\partial x}) \\\\\n= (2xz-yz)(4y-2x)+(2yz-xz)(-4x+2y) \\\\\n= 8xyz-4y^2z-4x^2z+2xyz - 8xyz + 4 y^2 z + 4x^2z -2xyz=0" holds.
Hence, given differential equation is integrable.
Now, "(2xz - yz) dx + (2yz - xz) dy - (x^2- xy + y^2) dz = 0"
"\\frac{2xdx+2ydy - (ydx+xdy)}{x^2+y^2-xy} = \\frac{dz}{z}"
Now, by integrating we get
"log(x^2+y^2-xy) = log(z)+log(c) \n\\\\ \\implies x^2+y^2-xy = cz" is the required solution.
Comments
Dear Ram, You are welcome. We are glad to be helpful. If you liked our service, please press a like-button beside the answer field. Thank you!
Thanks
Leave a comment